Robust bifunctional aluminium–salen catalysts for the preparation of cyclic carbonates from carbon dioxide and epoxides - Rulev, Yuri A.; Gugkaeva, Zalina; Maleev, Victor I.; North, Michael; Belokon, Yuri N. (Beilstein Journal of Organic Chemistry, 2015)
Two new one-component aluminium-based catalysts for the reaction between epoxides and carbon dioxide have been prepared. The catalysts are composed of aluminium–salen chloride complexes with trialkylammonium groups directly attached to the aromatic rings of the salen ligand. With terminal epoxides, the catalysts induced the formation of cyclic carbonates under mild reaction conditions (25–35 °C; 1–10 bar carbon dioxide pressure). However, with cyclohexene oxide under the same reaction conditions, the same catalysts induced the formation of polycarbonate. The catalysts could be recovered from the reaction mixture and reused.
Keywords: aluminium; carbon dioxide; cyclic carbonate; epoxide; salen